Detecção de nêutrons rápidos devido a radiação espalhada em aceleradores lineares - Nascimento, Débora Siqueira (2018)
Linear accelerators of high energy beams have been used to treat tumors in radiotherapy. Some questions about the protection of the patient and occupationally exposed workers have been arisen because high energy bundles generate scattered radiations that are undesirable in treatment. A possible radiation type generated due to the interaction of the beam with accelerator elements is the neutron, mainly fast neutrons. Such radiation can cause serious problems for patients besides cause damage to devices used by them. This work aims investigate the presence of fast neutrons around a mobile accelerator dedicated to intraoperative radiotherapy (IORT) using high energy electron beams. The aim is to detect the possible fast neutrons and further evaluate their distribution within phantom irradiated. For this study a mobile accelerator (LIAC), for electron beams, and a conventional accelerator (Elekta), for the photon beam, were used. Neutron measurements were made using bubble detectors (C-318) which are sensitive only to fast neutrons. In order to simulate the patient two polymethylmethacrylate (PMMA) phantoms, with a volume of 62 x 29 x 24 cm3 and 80 x 30 x 20 cm3, were used. Three detectors were positioned around the LIAC accelerator to measure the fast neutrons radiation generated by the accelerator elements. The measurements inside the phantom were made with three detectors positioned at three different depths, 5, 10 and 15 cm; 1, 5 and 10 cm. Moreover, two distances with respect to the central axis were chosen to the phantons irradiated by LIAC and Elekta: 0 and 4 cm; 0 and 30 cm, respectively. The results from the measurements around the LIAC demonstrate the abscense of fast neutrons. The results for both, LIAC and Elekta, showed that the dose of fast neutrons is mainly concentrated in the central axis and a decrease of 60% and 99%, respectively, in relation to off-axis doses. The highest values found for the different energies of 12, 10 and 8 MeV were 2.44, 1.14 and 0.59 uSv / Gy, respectively, for the LIAC. While the highest values for energies of 15, 10 and 6 MeV for Elekta were 2.98, 1.08 and 0.15 mSv/Gy, respectively. These results also showed the increasing ratio of dose to energy, both for Elekta and for LIAC. The relation between dose and depth also was discussed. It was found that in some cases the neutron attenuation increases with depth as expected while in others the ratio is not clear. The comparison between the doses established in each accelerator showed a difference around 10−3. The data presented in this work, therefore, demonstrate that the LIAC minimally generates fast neutrons within the phantom, when compared with the Elekta, and around were not detected for the LIAC. The neutrons generated by both accelerators presented similar behaviour within the phantom in relation to the energy variation, depth and central axis distance.